PENGARUH KARAKTERISTIK KEWIRAUSAHAAN TERHADAP MAHASISWA BERWIRAUSAHA DI ERA INDUSTRI 4.0 (STUDI PADA MAHASISWA PROGRAM STUDI ADMINISTRASI BISNIS FAKULTAS ILMU ADMINISTRASI UNIVERSITAS ISLAM MALANG) - yunita sari; Siti Saroh; dadang krisdianto (JIAGABI (Jurnal Ilmu Administrasi Niaga/Bisnis), 2020)
This research was conducted because the Business Administration study program was taught entrepreneurship courses in which one of them was taught about entrepreneurial characteristics. The purpose of this study was to determine the effect of entrepreneurial characteristics consisting of 10 indicators (dream, decisiviness, doers, determination, dedication, devotion, details, destiny, dollars, distribute) on student entrepreneurship in the industrial era 4.0. The research method used is a quantitative method. The sampling technique used in this study is judgmental sampling with a sample size of 45 respondents and using simple linear regression analysis techniques. The results showed that there was a positive and significant influence between the variables of entrepreneurial characteristics on entrepreneurial students. This is indicated by the t count of 4,305> t table 0,00058.